(iv)sin A1- cos Acosec A + cot A. please prove this using trigonometric identitiesi will mark the most appropriate one brainliest About the author Valentina

Answer: We need to prove 1+cosA 1−cosA =cosecA−cotA By taking L.H.S. = 1+cosA 1−cosA = 1+cosA 1−cosA × 1−cosA 1−cosA = 1−cos 2 A (1−cosA) 2 = sin 2 A (1−cosA) 2 = sinA 1−cosA = sinA 1 − sinA cosA =cosecA−cotA= R.H.S. Hence, proved Reply

Answer:We need to prove

1+cosA

1−cosA

=cosecA−cotA

By taking L.H.S. =

1+cosA

1−cosA

=

1+cosA

1−cosA

×

1−cosA

1−cosA

=

1−cos

2

A

(1−cosA)

2

=

sin

2

A

(1−cosA)

2

=

sinA

1−cosA

=

sinA

1

−

sinA

cosA

=cosecA−cotA= R.H.S.

Hence, proved